Factors affecting the fishermen household income and welfare - Lein, Alberto A.R.; Setiawina, Nyoman Djinar (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2018)
The desire to realize a prosperous society in the true sense is a great goal to be achieved by the Indonesian people in the system of government of the Republic of Indonesia. The potential of fishery resources can actually be utilized to increase income which will be expected to improve the welfare of fishermen households. In fact, many fishermen still have not been able to increase their catch, so the income level of fishermen households does not increase so that the welfare of the fishermans life is still not realized. The fishery sector is the mainstay for most people as if they depend on their fishing business. This phenomenon is occurring in most parts of Indonesia, including fishermen in the coastal area of East Flores. In relation to the phenomenon, then the research questions are 1). What is the effect of production cost, technology, selling price, and fish catch on the income of fishermen in East Flores Regency? 2). What is the effect of production cost, technology, selling price, and fish catch on the welfare of fishermen households in East Flores Regency? 3). Does the income of fishermen mediate the cost of production, technology, selling prices, and the fish caught on the welfare of fishermen households in East Flores District? Research objectives: 1). Analyzing, whether the factors of production costs, technology, the selling price of fish, and the catch of fish affect the income of fishermen in East Flores Regency? 2). Analyzing factors of production cost, technology, selling price, and fish catches have an effect on to fisherman household welfare in East Flores regency. 3). Analyzing whether fishermans income mediates the influence of production cost factor, technology, selling price and fish catch on fisherman households prosperity in East Flores Regency. The population of this study is 7,761 people. Sampling was conducted by applying "Slovin theory" so that the number of samples was 99 people. Proportionate Probability Sampling method was then applied in order to determine the number of respondents. The samples of 99 respondents were interviewed based on the questionnaires provided beforehand. In the interviews, the variables obtained consist of Production cost (IDR), technology (modern and traditional), sales price (IDR), and yields (Kg), Revenue (IDR), and welfare level (measured according to Standard Bureau of Statistics with 7 indicators, namely: consumption pattern, health, Education, Security, Love, Social and Culture). The cost of production, technology, selling price, and fish catch have a significant effect on fishermans income. Fishermen income has a positive and significant impact on the welfare of fishermen households in East Flores Regency. Indirect effect analysis found that factor of production cost, technology, and fish catch have significant influence through fisherman income to fisherman household welfare in East Flores Regency.